Perpustakaan Umum Tangerang Selatan Dan Ora Art Space Dengan Konsep Arsitektur Betawi Kontemporer - Noor, Ahmad Rifqy Rayhan; , Dr. Ir. Qomarun, MM (2017)
The growth of knowledge in all sector, like technology, social and culture, cause the society needs to get formation that accurate, complete, valid,and also up to date. A ibrary that have a complete collection would be very useful to blic society and also an academics. Unfortunately the society consciousness about the important of libraries to increase reading interest received less intention. Regional library of South Tangerang has a less attractive to visitor. erefore it needs to build another library that able to attract sitor and accompanied with additional facilities. Art space as an art gallery is considered able to synergize to attract people to the library. Moreover an Art Space can be a place for local artists to meet and gather with the people through art like, painting, sclupture, poet, music, and also atrical art. Contemporary architectural approach with imaging to Betawi culture is considered capable to provide rejuvenation on architectural Betawi culture which is monotonous. ication of Betawi contemporary architecture can be an identity of a building in South Tangerang City. Keywords: Art Space, Betawi Ora, Contemporary, Library, South Tangerang City